The effect of maggot formulated feed on essential amino acids composition, digestibility and growth of dwarf snakehead, channa gachua fry - Anik Martinah Hariati; Ating Yuniarti; Arifin, Nasrullah Bai; Muhammad Fakhri; Wiadnya, Dewa Gede Raka (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study was carried out to evaluate the influences of maggot formulated feed on growth, digestibility, feed utilization, and body composition of local snakehead Channa gachua. Five practical diets with iso-nitrogenous (40% protein) and caloric level (3.5 kcal g-1) were determined as 10%, 20%, 30% 40%, and 50% substitution of maggot to fish meal protein. Results demonstrated that replacement of 30% protein from maggot in the diet produced in the highest specific growth rate (4.41 %BW day-1). These results were in line with feed conversion ratio (FCR) and protein utilization (PER) at increasing dietary maggot level from 10% to 30%. Feed digestibility also attained the maximum level at 30% of maggot substitution. Thirty percent protein substitution from maggot meal exhibited the highest growth performance, nutrient utilization, and digestibility than other treatments. Dietary inclusion levels of maggot meal in diet above 30% remarkably influenced the growth, FCR, PER, and digestibility of C. gachua. Regarding feed price concern, the application of maggot meal may potentially be profitable for snakehead’s fry culture.